The Home Market, Trade, and Industrial Structure - Davis, Donald R. (American Economic Review, 1998)
Does national market size matter for industrial structure? This has been suggested by theoretical work on "home market" effects. In the present paper, I show that what previously was regarded as an assumption of convenience–transport costs only for the differentiated goods–matters a great deal. In a focal case in which differentiated and homogeneous goods have identical transport costs, the home market effect disappears. This paper discusses available evidence on the relative trade costs for differentiated and homogeneous goods. No compelling argument is found that market size will matter for industrial structure.